(untitled) (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstract This study was conducted based on the results pra survei that civil servants in performing basic tasks and functions indicated yet to reach optimum performance. This is presumably related to the implementation of policy leadership. Thus, the study aims to “Assessing the impact of policy leadership on work performance of employees at the District Secretariat or North Halmahera District’. ‘ This research applies descriptive method with quantitative approach. Purposive sample of respondents assigned as many as 80 employees, and data collection techniques distributed questionnaires to obtain primary data, secondary data obtained using the documentation techniques. All data and information obtained through surveys and direct observation techniques. After the data is collected. and then analysed using percentages applying analytical techniques (frequency table), followed by product moment correlation analysis and simple linear regression The results showed that: Policy-led governing the internal regulations of the Organization at the high category, while performance is still in the category of medium or medium. The leadership of the very significant effect and makes a great contribution to the achievement of the employment. When leaders adopt policies that encourage employee creativity and innovation, it will improve their work performance. Thus, it can that the hypothesis that "the leadership of the positive influence on job performance of employees at the District Secretariat North Halmahera" unacceptable and validity empirically tested at the same time justifying the underlying theories. Functional training required for top level so as to enhance the leadership skills of leadership and policies (internal policy of the organization) was an acceptable and capable to help creativity, innovation and motivate employees to perform better. Keywords: policy management, employee job performance